Basics of formalization of factors affecting the technology of restoration of building structures - Osipov, О. F.; Osipov, S. О. (Ways to Improve Construction Efficiency, 2023)
Currently, the priority direction of the technological development of the construction industry of Ukraine is the improvement of methods of restoration of construction structures and structures that have undergone destruction of varying degrees of intensity. The effectiveness of restoration technologies, along with the existing methods of performing works and mechanization of restoration processes, largely depends on the level of formalization of factors that affect the parameters of their restoration technology, taking into account the properties of restoration objects and the systemic property of the building as a complex structural system. The article describes the decomposition of the problem, the main principles and the adopted concept, which are the basis of the methodology of formalization of factors affecting the technology of restoration of damaged building structures during the restoration of destroyed buildings and structures, as well as in the conditions of reconstruction of buildings and restoration of architectural monuments. The formalization of influencing factors is based on the idea of patterns of interaction of restorative processes with the external environment, as a set of external factors that influence the process of transforming material elements into construction products. For the mathematical formalization of the problem of efficiency research, it is necessary to have numerical values of the coordinates, as which the values of factors and parameters are accepted (when solving the optimization problem at a detailed level) or the weighting factors or their estimates are accepted based on the results of previous studies and analysis of representative objects ( a priori information – when solving the optimization problem at the system level). The parameterization of influencing factors is based on idealizations - the construction of theoretical models, which are subsequently subject to formalization of one or another kind. Complexity categories are formed as a certain combination of the main features that describe, respectively, the characteristic construction and technological characteristics of the restoration object (reconstruction, restoration or destroyed object), the conditions of work production and the structural and technological parameters of the work front